1996
DOI: 10.4269/ajtmh.1996.55.655
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Mortality During and After Hospitalization in Western Kenya: Effect of Malaria Treatment Regimens

Abstract: Plasmodium falciparum infection is an important cause of the high childhood mortality rates in sub-Saharan Africa. Increasingly, the contribution of P. falciparum-associated severe anemia to pediatric mortality is being recognized while the impact of chloroquine resistance on mortality has not been evaluated. To address the issues of pediatric mortality, causes of death among hospitalized children less than five years of age in western Kenya were identified using standardized clinical examinations and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
3
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 0 publications
5
91
3
2
Order By: Relevance
“…Ultimately, with high levels of resistance, there is no clinical or parasitological response at all to treatment (¢gure 1). In high-transmission areas an increasing prevalence of anaemia may be the ¢rst sign of worsening drug resistance (Bloland et al 1998;Zucker et al 1996). As host factors also contribute signi¢cantly to the therapeutic response in malaria, there tends to be a poor correlation between in vitro and in vivo antimalarial drug susceptibility responses.…”
Section: (G) Assessment Of Drug Responsesmentioning
confidence: 99%
“…Ultimately, with high levels of resistance, there is no clinical or parasitological response at all to treatment (¢gure 1). In high-transmission areas an increasing prevalence of anaemia may be the ¢rst sign of worsening drug resistance (Bloland et al 1998;Zucker et al 1996). As host factors also contribute signi¢cantly to the therapeutic response in malaria, there tends to be a poor correlation between in vitro and in vivo antimalarial drug susceptibility responses.…”
Section: (G) Assessment Of Drug Responsesmentioning
confidence: 99%
“…We identified eight prospective hospital-based studies conducted in African settings that had reported mortality rates associated with severe malarial anemia between 1990 and 1997 6,7,16,18,19,[26][27][28] (Table 1). The average risk of mortality was 12%, but the heterogeneity was significant (P Ͻ 0.001, by chi-square test).…”
Section: Resultsmentioning
confidence: 99%
“…21,33 Furthermore, the mortality risk may vary depending on several clinical characteristics, such as respiratory distress, impaired consciousness, age, hemoglobin level, parasite density, and comorbidity. 7,[16][17][18][19][20][21][22] Transfusion was not beneficial when the patient's risk of mortality without a transfusion was Ͻ 5%. Because most deaths among severely anemic children tend to occur within 12 hr of admission, it is important to identify those patients at high risk timely to allow for early intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations